Parenting Styles and Their Impact on Children’s Behavior in Dahl’s Charlie and The Chocolate Factory - Desy Eva laila Rokhmah; Martha Betaubun (Hasanuddin University, 2021)
Parenting is a necessary component of human development. It assists children in developing the competencies necessary to function in and face society as adults. A good parenting approach would assist the child in functioning optimally in the society; on the other hand, a poor parenting practice would increase the child's susceptibility to negative behavior and ultimately ruin the child's future. This paper aims to demonstrate Dahl's portrayal of parenting styles and their effect on children’s behavior in Charlie and the Chocolate Factory. The study was performed using the psychology of literature approach, with Baumrind's parenting framework serving as the underlying theory. The finding demonstrates that parental parenting styles serve as the